Indirect fluorescent antibody technique in the serology of Toxoplasma gondii. Issue 2 (March 1965) - Fletcher, S.
Abstract : The indirect fluorescent antibody technique has been used to titrate patients' antibody against Toxoplasma gondii. Rigorous tests of the immunological validity of the method were made. The reactions of the gamma globulin of human immune serum with Toxoplasma gondii and fluorescent rabbit anti-human gamma globulin were thus shown to be specific. Thereafter the technique could be used with confidence to detect the reaction between doubling dilutions of patient's serum and smears of unfixed Toxoplasma gondii. In this way, titres were obtained with the indirect fluorescent antibody technique which agreed well with those of the dye test at both low and high levels of antibody. Compared with the dye test, the indirect fluorescent antibody technique has many advantages. The end-point is sharp and obviates the counting of stained and unstained organisms; supplies of antibody-free accessory factor sera are not needed; prozones undetected by the dye test are strongly positive at screening dilutions, the reagents keep indefinitely and lend themselves to preparation, standardization, and issue by a central reference laboratory.